Chapter 3 The instruments of European heritage - Zito, Anthony R. (Taylor & Francis, 2019)
This chapter differs from others in this monograph in its focus on two political organisations, the EU and the COE, and their top-down efforts to engage with issues of heritage and identity. These organisations represent the two most visible post-1945 political efforts to transform Europe as a region, by promoting further integration; both are driven by a fluid collective memory of the impact made by world wars, genocide, economic deprivation and other forms of societal disruption. By their very nature, both organisations have sought to engage with the construction and reconstruction of history and identity, both to pursue a vision of a common Europe and to build a sense of purpose and value in their organisational efforts to build integration (and therefore justify their existence). They have selected particular policy instruments, which Hood (1983) defines as the tools by which actors implement their governance strategies. The core research question is: how do these two institutions seek to intervene and make people engage with memories, histories and identities by creating cultural heritage institutions and instruments?